OPTIMALISASI KOMUNIKASI BENCANA DALAM MENGURANGI KABUT ASAP DI PROVINSI RIAU - Rohayati, Rohayati; Alhidayatillah, Nur (Universitas Medan Area, 2020)
This study aims to identify the optimization of disaster communication in reducing haze, using a qualitative descriptive approach. The results show that the implementation of disaster communication has been carried out optimally by BPBD of Riau Province, it can be seen from various factors that have been implemented related to disaster communication. These four factors are Costomer Focus, Leadership commitment, Situational awareness, and Media partnership. Although the four factors are also influenced by other things that occur in the field, such as human error, land exploration by companies and weather conditions. This research can be a reference for stakeholders or the government related to the handling of haze. Further in-depth research is needed related to disaster communication in Riau Province, so that the haze problem that occurs every year can be handled optimally